Computational Thinking Process of Prospective Mathematics Teachers in Solving PISA Model Problems - Gunawan, Gunawan; Setiyani, Setiyani; Widiyastuti, Erni; Akhsani, Lukmanul; Herdian, Herdian (Jurnal Pendidikan MIPA, 2024)
The research outlines the computational thinking process that prospective mathematics teachers use to solve PISA model problems. The Department of Mathematics Education conducted the research on 32 students in the Basic Mathematics course. This qualitative approach research used research instrument such as a computational thinking skill test and interview guidelines. The researchers grouped students into low, medium, and high ability categories based on previous tests. The researchers took as many informants as possible from each category using purposive sampling techniques. The applied technical data analysis included data reduction, presentation, and conclusions. The computational thinking process consisted of orientation, abstraction, decomposition, algorithms, and evaluation. The study provided several results, including high- and medium-category students being able to write information at the orientation and algorithm stages. The difference between the computational thinking processes of low- and medium-category students lies in the orientation stage and algorithms. Low-category students had to be more detailed in recording every step of the problem-solving process, as they could not write down all the primary information and problems. Those three lied in the orientation stage, the process of identifying information, and the key problems at the orientation stage as an early and important aspect of the computational thinking process. This research facilitates teachers improve students' computational thinking in solving high-level problems.         Keywords: computational thinking process, PISA model problems, problem-solving DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp961-971